2017
DOI: 10.4025/actasciagron.v39i2.30773
|View full text |Cite
|
Sign up to set email alerts
|

<b>Breeding new improved clones for strawberry production in Brazil

Abstract: ABSTRACT. Breeding different strawberry genotypes and plant selection in Brazil could result in new cultivars with better environmental adaptations. The aim was to develop and select new F 1 strawberry plants with higher potential yields. Twelve hybrid populations were obtained from breeding the cultivars Aromas, Camarosa, Dover, Festival, Oso Grande, Sweet Charlie and Tudla, and 42 F 1 hybrids were obtained from each population. An augmented randomized block design was used. Productive traits were measured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 4 publications
(7 reference statements)
1
14
3
1
Order By: Relevance
“…High variability was observed among the assessed hybrids, with AMCF being the only trait that did not significantly differ between hybrids. These results are different from those that were found by Galvão et al [12] and Vieira et al [11], who assessed strawberry hybrids and found significant differences for all of the traits related to yield. No differences were found for soluble solids, titratable acidity, pH, and anthocyanins.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…High variability was observed among the assessed hybrids, with AMCF being the only trait that did not significantly differ between hybrids. These results are different from those that were found by Galvão et al [12] and Vieira et al [11], who assessed strawberry hybrids and found significant differences for all of the traits related to yield. No differences were found for soluble solids, titratable acidity, pH, and anthocyanins.…”
Section: Discussioncontrasting
confidence: 99%
“…After crossing, formation, and development of fruits, the achene's were removed, dried, acid scarified, and germinated in vitro, as described by Galvão et al [12].The seedlings were transplanted into 72-cell polypropylene trays containing bio-stabilized pine bark substrate when they reached four to five true and expanded leaves, i.e., at 60 days after germination.…”
Section: Crossbreeding and Obtaining Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strawberry crops (Fragaria x ananassa Duch) have a wide geographic distribution (Morales et al 2012). Most of the genotypes of commercially grown strawberries in Brazil originate from genetic improvement programs in the United States (Galvão et al 2017), and they are not well adapted to the diverse edaphoclimatic conditions existing in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…2013) . Esta especie es cultivada en países ubicados, tanto en la zona tropical como templada del mundo, principalmente, en el continente europeo y americano (Galvão et al . 2017) .…”
Section: Introductionunclassified